Comparative Analysis of Transportation Methods in The Distribution of Frozen Chicken Products - Amirah Nova Khairiyah Pane; Elsa Sri Erjuni Rumapea; Elsa Putri Pertiwi; Dinda Azzahara Salzabillah; Nia Gracia Banik; Devi Ramuna (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2026)
Distribution is a critical component of logistics systems, especially in the food industry where perishable products such as frozen chicken require strict temperature control and timely delivery. CV XYZ, a frozen chicken distributor in Batam, encounters several operational challenges, including high transportation costs, limited cold chain infrastructure, and inefficient allocation of distribution routes. These issues not only increase operational expenses but also pose risks to product quality and delivery reliability. Therefore, an effective distribution strategy is required to ensure cost efficiency and service performance. This study aims to identify the most efficient transportation method to minimize distribution costs by applying three initial solution approaches: North West Corner Rule (NWCR), Least Cost (LC), and Vogel’s Approximation Method (VAM). The solutions obtained from each method were further evaluated using the Stepping Stone method to test their optimality. This research adopts a quantitative approach using a mathematical transportation model, with data collected through interviews and direct field observations. The results show that the VAM method produces the lowest initial distribution cost of Rp57,062,000, compared to Rp60,022,000 for the LC method and Rp63,916,000 for the NWCR method. After optimality testing, only the VAM solution remained unchanged, indicating that it had already reached optimality. Thus, VAM is recommended as the most effective method for optimizing frozen chicken distribution costs at CV XYZ Batam.